The Design of Solar Cell-Based Street Lighting for School Area - Azriyenni Azhari Zakri; Muhammad Fauzan; Wahri Sunanda; Rudy Kurniawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
Currently, public street lighting using Solar-based Public Street Lighting has been widely used. Solar-based Public Street Lighting is an off-grid Solar Power Plant application for street lighting. This study aims to use Solar-based Public Street Lighting which has been designed for Inayah Islamic School according to the geographical features of the school. To design this Solar-based Public Street Lighting by considering the economic aspect. From the data obtained directly at the location, the road width is 4.5 meters and the total length is 330 meters. Road size is used to determine the need for lighting quality according to the Indonesian National Standard of 7391:2008. This Solar-based Public Street Lighting has been designed with a pole height of 5 meters and a 1.5-meter pole arm using a 20 Watt 2-in-1 LED lamp and a solar cell capacity of 50 Wp per pole. From the results of the design analysis, the component specifications used in the design have met the requirements according to SNI of 7391:2008, and the required poles for Solar-based Public Street Lighting are 22 points for the Inayah Islamic School Complex area